Analysis Of Processed Cash Product Development Using Quality Function Deploment (QFD) Method In UD. Mete Mubaraq Lombe Kendari City - Febriani Febriani; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the process of developing cashew products using the Quality Function Deployment (QFD) method at UD. Cashew Mubaraq Lombe Kendari City. Determination of the research location purposively. Data was collected using observation, questionnaires, interviews, and documentation. Theanalytical method used is Quality Function Deployment (QFD). The results showed the development of cashew products at UD. Mubaraq Lombe cashew using the QFD method, it was found that the priorities to be developed in accordance with the wishes and needs of consumers in a row include: (1) the selling price ofcashew products is affordable (8.430%), (2) sales discounts on certain days (7.686%) , (3) discounted cashew product purchases (7.270%), (4) cashew product sales online (6.822%), (5) easy to get cashew products (6.623%), (6) does not contain preservatives (6.567%) , (7) good product quality (6,435%), (8) product taste (6,410%), (9) information on nutritional value on cashew product packaging (6,384%), (10) price match with product quality (8,430%) , (11) there is a certificate of permission from the Ministry of Health (department of health) for cashew products (6.255%), (12) there are halal certificates and labels for cashew products (6.230%), (13) information on expiration (expiration date) (6.229%), (14 ) various types of cashew products (6,227%), and (15) attractive product packaging designs (6,152%).